1984
DOI: 10.1152/ajpheart.1984.246.6.h838
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of parasympathetic control of heart rate by a noninvasive method

Abstract: The degree of parasympathetic control of heart rate was assessed by the abolition of respiratory sinus arrhythmia with atropine. Peak-to-peak variations in heart periods (VHP) before atropine injection correlated significantly (r = 0.90, P less than 0.001) with parasympathetic control, indicating that VHP alone may be used as a noninvasive indicator of the parasympathetic control of heart rate. Pharmacologic blockade of beta-adrenergic supply in a separate group of normal volunteers did not alter the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
138
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 0 publications
7
138
0
3
Order By: Relevance
“…These variations are largely attributable to respiratory modulation of the outflow of the vagal nerve: the larger the respiratory sinus arrhythmia, the stronger the vagal control of heart rate. 11 Respiratory sinus arrhythmia was measured as described previously. 16,17 Respiratory sinus arrhythmia reactivity was calculated by subtracting the respiratory sinus arrhythmia during the stress tasks from the respiratory sinus arrhythmia at rest.…”
Section: Measurementsmentioning
confidence: 99%
“…These variations are largely attributable to respiratory modulation of the outflow of the vagal nerve: the larger the respiratory sinus arrhythmia, the stronger the vagal control of heart rate. 11 Respiratory sinus arrhythmia was measured as described previously. 16,17 Respiratory sinus arrhythmia reactivity was calculated by subtracting the respiratory sinus arrhythmia during the stress tasks from the respiratory sinus arrhythmia at rest.…”
Section: Measurementsmentioning
confidence: 99%
“…22 The HF component is equivalent to respiratory sinus arrhythmia and is thought to reflect vagal control of heart rate. 23 The TP, LF, or variance are components mediated by both sympathetic and vagal efferent activity. 24 The ratio of LF to HF (LF/HF) and LF in normalized units (LF%) are thought by some investigators to mirror sympathovagal balance or reflect sympathetic modulation, the HF in normalized units (HF%) responses to sympathetic inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,19 Low-frequency power is believed to reflect the modulation of sympathetic and parasympathetic tones, 16 whereas high-frequency power is believed to reflect pure parasympathetic tone. 17 Although the precise physiologic meaning of very-low-frequency power is not completely understood, it has been suggested that very-lowfrequency power is influenced by thermoregulation, fluctuation in the renin-angiotensin axis, Gehi et al …”
mentioning
confidence: 99%
“…The software also computed frequency-domain variables using a fastFourier transformation over the 24-hour period, including very-low-frequency power (0.0033 to 0.04 Hz), low-frequency power (0.04 to 0.15 Hz), high-frequency power (0.15 to 0.4 Hz), and wideband frequency power (0.0033 to 0.4 Hz) in square milliseconds. 12,16,17 Very-lowfrequency power and wideband frequency power were available for only 478 participants because the software was upgraded during the study. In a quality control check, we performed blinded repeat measurements of 20 tapes and found >99% concordance in readings between the 2 software programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation